Homework in the Countries of the Visegrad Group (V4): a Comparative Legal Study - Richter-Sitko, Norbert; Barański, Michał (Review of European and Comparative Law, 2026)
Derived from the traditional cottage industry, homework has played a significant social and economic role in Europe for centuries. In the digital economy era, homework is acquiring new significance, particularly in the context of flexible forms of work, such as remote working or home-based platform work. This article focuses on the Visegrad Group countries, analyzing the regulation of homework within each country’s national legal system. This analysis will help determine the status of homework within labor law and its legal position. To this end, the authors employed a historical approach to examine the evolution of homework, a dogmatic approach to establish its legal standing in relation to the employment relationship and contract, and a comparative approach to identify convergences in national regulations. The final result of the comparative study reveals the diversity of homework regulations within the Visegrad Group. These range from a shift towards remote work (Czech Republic), through to separate yet compatible regulations on telework and homework within the employment relationship (Slovakia and Hungary), to the distinction between remote work and homework (Poland).